BAHASA ARAB DAN BAHASA AL-QUR’AN - Moh Aman (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2021)
This research is a library research with a qualitative approach. This research concludes, that Arabic and the language of the al-Qur’an when viewed from a literary standpoint, both have something in common, namely that both are the source and origin of all languages that exist on this earth. When viewed from the side of uniqueness, both of them also have the same uniqueness, namely the beauty of literature that does not diminish the slightest strength of the material content, this is different from other languages. Even when viewed from the concept of kalam both in the form of orders and prohibitions, both of them also have similarities. However, the fact proves that the language of the al-Qur’an still has advantages over Arabic, this is evident from the Arabic poets who are unable to compose literary works that are the same as the language of the al-Qur’an. This is because there are differences in the choice of words, the words contained in the al-Qur'an are not only beautiful in their series, but the meaning contained in these word choices really makes the al-Qur'an superior to Arabic. The words chosen by Allah the Lord of the worlds, cannot be matched by the choices of humans, so that the language of the al-Qur'an becomes an extraordinary language which is also a miracle.